2017
DOI: 10.1093/neuros/nyw124
|View full text |Cite|
|
Sign up to set email alerts
|

Interhospital Transfer of Neurosurgical Patients: Implications of Timing on Hospital Course and Clinical Outcomes

Abstract: The timing of transfer arrivals, both by hour or day of the week, is correlated with the time to intervention, hospital course, and overall patient outcomes. Patients admitted during the weekend suffered worse functional outcomes and a trend towards increased mortality. While transfer logistics clearly impact patient outcomes, further work is needed to understand these complex relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…7 As a result, delays in the transfer of patients with sICH would result in worse outcomes. 8,9 At our urban, academic, tertiary care center, the neurocritical care unit (NCCU) is the preferable unit to receive sICH patients, especially those in need of EVD placement, from referring facilities. Historically, when there was no immediately available bed in the NCCU, patients were transferred to any adult intensive care unit (ICU) with an available bed.…”
Section: Introductionmentioning
confidence: 99%
“…7 As a result, delays in the transfer of patients with sICH would result in worse outcomes. 8,9 At our urban, academic, tertiary care center, the neurocritical care unit (NCCU) is the preferable unit to receive sICH patients, especially those in need of EVD placement, from referring facilities. Historically, when there was no immediately available bed in the NCCU, patients were transferred to any adult intensive care unit (ICU) with an available bed.…”
Section: Introductionmentioning
confidence: 99%
“…Avoidance of interfacility transfer is associated with potential cost savings [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [22] . Arnold et al retrospectively reviewed the records of TBI patients with GCS 13–15 transferred to a level 1 trauma center in their respective hospital system.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is a common reason for transfer to trauma centers for neurosurgical evaluation [1] , [2] , [3] , [4] , [5] , [6] . Results from a recent TRACK-TBI study revealed that less than 50% of patients with so-called “mild” TBI (i.e., Glasgow Coma Score (GCS), 13–15) reported full return to pre-injury levels of day-to-day function at one-year post-injury [7] , highlighting the need for further study of long-term functional limitations in this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that 17% of neurosurgical patients transferred to one hospital bypassed another neurosurgical center en route, and that in-transfer clinical decline occurred less frequently in patients who were transferred to the nearest neurosurgery center [3]. Furthermore, Holland et al demonstrated that the majority of transfers at their institution occurred at night despite a near equal number of requests during the daytime [1]. They also found that weekend transfers tended to have poorer outcomes than weekday transfers [1].…”
Section: Introductionmentioning
confidence: 99%
“…This holds true emphatically for neurosurgical patients, for whom both avoidable IHT and inefficient transfer infrastructure leave room for quality improvement. In one series of neurosurgical patients, 57.4% of IHT led to no surgical intervention and in another one 34.5% IHTs were non-operative [1,2]. The direct transportation costs for avoidable transfers amounted to $1.46 million over two years in a study of neurosurgical IHT [2].…”
Section: Introductionmentioning
confidence: 99%